A simple approach for air-gap permeance calculations in double excitation synchronous motor modelling with reluctance network - Trung-Kien Hoang; L. Vido; Dinh-Quang Nguyen (Vietnam Journal of Science, Technology and Engineering, 2021)
This article proposes an easy-to-use approximation for air-gap permeance calculations in a reluctance network. An extension of the overlap area between the stator and its corresponding rotor tooth to a position where the permeance becomes zero is also proposed. The advantage of this method is the simplification of conventional complex reluctance calculations while maintaining high accuracy. The proposed approach is applied to a double excitation synchronous motor, which usually requires a 3D simulation tool for the calculations. The validation of the accuracy of the proposed method on the flux linkage, back EMF, and electromagnetic torque are accomplished by comparison with those obtained from a conventional method and experimental data. The results of the comparison recommend the use of the proposed method for different electrical motor geometries.